(untitled) (Leadership, Education, Personality: An Interdisciplinary Journal, ISSN: 2524-6178, 2025)
This research investigates the correlation between cultural diversity and workplace innovation. By examining diverse organizations, the study explores how cultural differences impact creativity, problem-solving, and overall organizational performance. It aims to identify factors that facilitate or hinder the integration of diverse perspectives and contribute to a more innovative work environment.